Analysis of Negative Aggressiveness Behavior Based on Gender In Members of Tadjimalela Martial Arts College - Siti Azizah Fauziah; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Tadulako Journal Sport Sciences And Physical Education, 2026)
Adolescent behavior in training environments still shows a tendency toward aggression. This situation is important to examine, given its potential conflict with the philosophical values ​​of pencak silat, which emphasize self-control, discipline, and courage. This study aims to analyze forms of gender-based negative aggressiveness behavior in members aged 12-15 years, as well as analyze the role of coaches in fostering and managing aggressive behavior. This study uses a qualitative approach with a case study design, the research subjects consist of members who are actively practicing aged 12-15 years, parents, and coaches. Data was collected through questionnaires, interviews, and observations. Then, it is analyzed through continuous data reduction, data presentation, and verification, with the help of Nvivo12 software. The results showed that aggressiveness was manifested in the form of verbal aggressiveness, physical aggressiveness, anger, and hostility, with verbal aggressiveness being the most dominant based on interviews and observations. Meanwhile, the results of the questionnaire showed that the tendency of aggressiveness was in the low to medium category. There is a difference in aggressiveness based on gender, where male members show a higher tendency than women. Coaches play a role through direct reprimands, punishment, and instilling the values of the panca dharma, as a preventive strategy. This research contributes to enriching the study of adolescent aggressiveness in the context of value-based martial arts, as well as providing implications for character development in the training environment.